2008
DOI: 10.1159/000146070
|View full text |Cite
|
Sign up to set email alerts
|

First-Episode Psychosis: Diagnostic Stability over One and Two Years

Abstract: Background: Diagnostic stability is important for daily clinical work and planning of treatment. The aims of this study were to measure diagnostic stability in a clinical epidemiologic sample and to identify markers of change in diagnosis. Sampling and Methods: Diagnostic stability and change were measured in a sample of 301 patients with first-episode psychosis from four national health care sectors in Norway and Denmark at baseline, 1 and 2 years. Results: Diagnostic stabilities were high for schizophrenia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
2
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 38 publications
1
53
2
7
Order By: Relevance
“…Further, we found that schizophrenia was the most stable diagnosis over time and that most diagnostic shifts were to schizophrenia and schizophrenia spectrum disorders. These findings replicate those of several other studies [2][3][4][5][7][8][9] conducted with samples of patients in different countries and indicate that schizophrenia is reliably diagnosed even in the early phases of the illness. Conversely, schizophreniform disorder and psychosis NOS were found to be among the least stable diagnoses, as has been observed in numerous other studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Further, we found that schizophrenia was the most stable diagnosis over time and that most diagnostic shifts were to schizophrenia and schizophrenia spectrum disorders. These findings replicate those of several other studies [2][3][4][5][7][8][9] conducted with samples of patients in different countries and indicate that schizophrenia is reliably diagnosed even in the early phases of the illness. Conversely, schizophreniform disorder and psychosis NOS were found to be among the least stable diagnoses, as has been observed in numerous other studies.…”
Section: Discussionsupporting
confidence: 90%
“…This figure is in keeping with several studies that have found overall stabilities ranging from 67% to 77%. [2][3][4][5]7 However, it is important to note that while most of these studies included diagnoses of organic psychotic disorder, substance-induced psychotic disorder, and brief psychotic disorder, these diagnoses are excluded from admission to the PEPP-Montreal program. Further, we found that schizophrenia was the most stable diagnosis over time and that most diagnostic shifts were to schizophrenia and schizophrenia spectrum disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Conversely, there is evidence suggesting good stability levels for the diagnosis of schizoaffective disorder in first-episode psychosis patients. 40,41 The latter results are probably related to the fact that these diagnoses were performed in research contexts, in large cohorts of cases with first-episode psychosis, and using scales and diagnostic interviews administered by experienced professionals.…”
Section: Validity Of the Psychiatric Diagnosismentioning
confidence: 99%
“…"Diagnostic shifts" (Bromet et al, 2011) may reflect inter-rater variation, changes in available information, the evolution of illness or a combination of all of these (Bromet et al, 2011;Haahr et al, 2008 uncertainty; it is difficult to judge causation of psychosis when substance use persists (Mathias et al, 2008). Second, substance use may influence the course of psychosis.…”
Section: Introductionmentioning
confidence: 99%